Rancang Bangun Sistem Informasi Monitoring Laporan Inventory Control PT.Daiichi Elevator Indonesia - Euis Sitinur Aisyah; Devi Finastika; Nia Kurniasih (UNIVERSITAS RAHARJA, 2020)
PT. Daiichi Elevator Indonesia is a company engaged in the sale of elevators, escalators and spare parts. PT. Daiichi Elevator Indonesia applies a single agent from the Chinese company Daiichi Seloon. In the monitoring inventory control system PT. Daiichi Elevator Indonesia. Found some weaknesses of the system such as making safety reports still running manually and not complicated so that planning and data processing is still found some input errors that occur have not been properly computerized, in accordance with the request, so it needs to be designed as a computerized system and equipped with both to produce true and accurate information. This study discusses systems that provide the latest information and provide users as admin and users in the system to input, process, and output preparations. By using the interview method, observation on the system and the PIECES analysis method to see the strength of the company to support this monitoring system also uses the PHP programming language using a database using MySQL, as well as making that is poured using UML (Unified Modeling Language) using diagrams such as use case , activity. In terms of analyzing the existing system at PT Daiichi Elevator Indonesia, it is expected that the admin will no longer make company inventory reports, because the data that will be made into inventory reports will be automatically processed and become print-ready reports through the system.